Can Prosuming Become Perilous? Exploring Systems of Control and Domestic Abuse in the Smart Homes of the Future - Sovacool, Benjamin; Furszyfer-Del Rio, Dylan D; Martiskainen, Mari (Frontiers in Energy Research, 2021)
In what ways can new, emerging digital technologies and energy business models such as “prosuming” become intertwined with troubling patterns of domestic abuse and violence? Domestic violence entails controlling, coercive or threatening behaviours, to gain or maintain power and control between intimate partners or family members regardless of gender or sexuality. The rapid development of digital communication services, smart homes, and digitalization processes such as prosuming create surprising threats related to technology-facilitated abuse. In this empirical study, based on a nationally representative survey of householders (n=1032 respondents) and three focus groups with the general public in different locations around the UK (n=18 respondents), we explore the extent that prosuming technologies, smart grids and smart systems could act as potential enablers of domestic violence or systems of control. We also explore the use of smart systems as possible deterrents and mechanisms to reduce and address domestic violence and provide victim protection and recovery. In doing so, we explore user perceptions and preferences of smart systems, in relation to trust, monitoring, tracking, and surveillance. We finally discuss our results through the themes of duality and policy and provide conclusions with recommendations for further research.